Ambon Banana-Tree Sap stimulated Endothelial Cell Migration in Human Umbilical Vein Endothelial Cells (HUVECs) Induced with Inflammatory Mediator IL-1 - Provisia Marthalita Yuning Wulan; Maria Juliana Dorothy; Resha Alinda; Kristianingrum Dian Sofiana; Bunga Prihardina; Nur Permaasari; M. Aris Widodo (Journal of Tropical Life Science, 2019)
Ambon banana-tree (Musa paradisiaca var.sapientum) sap (ABT sap) contains active substances that can stimulate the wound healing process such as: flavonoid, saponin, ascorbic acid. Those substances are needed in an important phase of wound healing called angiogenesis through activation of Vascular Endothelial Growth Factor (VEGF) pathway that stimulates actin reorganization in endothelial cell migration and proliferation. The aim of this study is to evaluate the effectiveness of banana-tree sap in stimulating cells migration, VEGF and nitric oxide (NO) level in Human Umbilical Vein Endothelial Cells (HUVECs) culture that induced by pro-inflammatory cytokine IL-1 (Interleukin-1). The ABT sap was obtained by pressing a fresh Ambon banana stem, then was mixed with culture medium into 0.125%, 0.25% and 0.5% concentration. The ABT sap then was used for treating HUVECs cell that induced by IL-1 200 ng/mL for 48-hours. The result of this study shows that Ambon banana-tree sap increased HUVECs cell migration. However, after 48-hours treatment with ABT sap showed no difference in the VEGF and NO level in the culture media. These results suggested ABT sap able to increase migration to HUVECs that promising for wound healing agent. Therefore, the further research to elucidate the detailed mechanism and identify the active compound warrant to be done.